PERGESERAN KONSEP NARKOTIKA DALAM SISTEM HUKUM INDONESIA - Rifqi Ridlo Phahlevy; Maghfiroh . (Fakultas Hukum, Universitas Muhammadiyah Pontianak, 2019)
The regulation of narcotics in Indonesia began in the New Order era with the enactment of Law No. 22/1997 concerning Narcotics. However, in the reform era, there were revisions to the narcotics law with the enactment of the new narcotics law, which was Law No. 35/2009 concerning narcotics. This study applies a normative method based on the statutory approach and conceptual approach. This study aims to understand the shift in the concept of narcotics in Indonesia after the enactment of law 35/2009 and the concept of narcotics in Islamic law. After the enactment of law No. 35/2009 concerning narcotics, there was a shift in the concept of narcotics, which are substantial and essential in the form of changes and additions to the law No 35/2009 concerning narcotics. The amendment is related to several definitions that exist in the narcotics law, along with the addition of existing definitions in general provisions such as the definition of narcotics precursors and the definition of narcotics abuse. The concept of narcotics in Indonesia has an essential closeness to the concept of narcotics in Islamic law because narcotics and chemistry have similarities in terms of illat (legal reasons).Keywords: Narcotics, Shariah Perspectives, Shifting concepts.